A hierarchical porous adsorbent of nano-α-Fe2O3/Fe3O4 on bamboo biochar (HPA-Fe/C-B) for the removal of phosphate from water. (October 2018) - Zhu, Zongqiang; Huang, C.P.; Zhu, Yinian; Wei, Wenhui; Qin, Hui
Graphical abstract: Highlights: An α-Fe2 O3 /Fe3 O4 adsorbent supported on multi-porous bamboo wood biochar is synthesized. The optimal pH for phosphate adsorption is 3.0. The adsorption capacity is 2.46, 2.62, and 2.81 mg-P/g at 25, 35, and 45 °C, respectively. Multiple-stage, intra-particle diffusion model describes well the kinetics of adsorption. Langmuir isotherm fits data well in three distinct regions of phosphorus concentration. Abstract: A novel and magnetic hierarchical porous adsorbent functionalized by coating α-Fe2 O3 /Fe3 O4 on bamboo biochar (HPA-Fe/C-B) is prepared and tested for the removal of phosphorus from aqueous solutions. The effect of phosphorus (P) concentration, temperature, pH, adsorbent grain size, adsorbent dosage, and contact time on phosphorus adsorption is investigated. Results show that by increasing the initial concentration from 2 to 10 mg-P/L, the phosphorus adsorption capacity of HPA-Fe/C-B ( d g 0.11 mm and contact time 12 h) increases from 0.20 to 2.46, 2.64, and 2.81 mg-P/g and the phosphorus removal is reduced from 99.2 to 49.2 wt%, 99.4–52.8 wt% and 98.8–55.4 wt%, at temperature of 25, 35, and 45 °C, respectively. The phosphorus adsorption capacity of the unpulverized HPA-Fe/C-B ( d g 1.59 mm) is from 0.18 to 0.66 mg-P/g in the concentration range of 2–10 mg-P/L, respectively, which is in the same order of magnitude as that of pulverized HPA-Fe/C-B or nano-size iron adsorbents reported in the literature. Kinetic and equilibrium adsorption results fitted well by the intra-particle diffusion and the Langmuir adsorption isotherm, respectively.